Mechanism of the Fibroblast Growth Factor 23/α-Klotho Axis in Peripheral Blood Mononuclear Cell Inflammation in Alzheimer's Disease. (4th July 2022) - Li, Baoshan; Zhou, Min; Peng, Jing; Yang, Qiao; Chu, Jingxin; Li, Ruoqing; Jiang, Yi
ABSTRACT: Alzheimer's disease (AD) is a prevalent type of dementia and threatens the health of most elderly people and poses a huge burden to families and society. The fibroblast growth factor 23 (FGF23)/α-Klotho axis is associated with multiple aging-related diseases. Hence, this study explored the mechanism of the FGF23/α-Klotho axis in AD. FGF23/α-Klotho protein contents and levels of inflammatory cytokines in AD patients were measured, and the correlation between FGF23/α-Klotho protein contents and inflammatory cytokines was analyzed. FGF23 and α-Klotho expressions were blocked in peripheral blood mononuclear cells (PBMCs) in AD patients (AD-PBMCs) to assess the effects on cell inflammation and the Wnt/β-catenin pathway activation. The Wnt/β-catenin pathway was inhibited to evaluate cell inflammation. Combined treatments of the cells were conducted to verify the role of the FGF23/α-Klotho axis and the Wnt/β-catenin pathway in inflammation in AD-PBMCs. Increased FGF23 protein concentration and reduced α-Klotho protein concentration were observed in AD patients and correlated with inflammatory cytokine levels. FGF23 inhibition or α-Klotho overexpression reduced the production of inflammatory cytokines and activated the Wnt/β-catenin pathway in AD-PBMCs. Blocking the Wnt/β-catenin pathway increased inflammatory cytokine production in AD-PBMCs and annulled the effects of the FGF23/α-Klotho axis on AD-induced cell inflammation. We concluded that the FGF23/α-Klotho axis can regulate the AD-induced cell inflammation through the Wnt/β-catenin pathway.